Le procès de Tôkyô et le débat sur l’Histoire de Shôwa - Tristan Brunet (Droit et Cultures, 2009)
Published in 1955, the History of Shôwa is the most prominent example of the project by Japanese academic historians to elaborate a new national history, in the aftermath of the Second World War. Their intended goal was to exceed the limits of the Tokyo trial, and the threat those limits put, according to the authors, on the Japanese democracy. A polemic took place after the publication of the book, which allows us to acknowledge the growing resistance within Japanese society against such a project. This paper will try to underline the political and memorial stakes behind this debate, especially in relation to the responsibilities of war, and consequently the depiction of the Tokyo trial in such an history.